The use of accounting information in the management of micro and small enterprises in the municipality of Poção/Brazil (Revista Brasileira de Contabilidade e Gestão, 2022)
The objective of this study has been to investigate the use of accounting information in the management of micro and small enterprises in the municipality of Poção, located in the State of Pernambuco, Brazil. By establishing this objective, the research intends to contribute to the study of the use of accounting information in the management of micro and small enterprises. The research is characterized as descriptive with a quantitative approach, and it has involved field research with the application of a questionnaire to micro and small entrepreneurs in the municipality of Poção. The results have revealed, among other aspects, that most micro and small entrepreneurs who have an accountant in their company use accounting information for decision-making. On the other hand, although 87.9% of the respondents recognize the importance of accounting information for management, 36.4% do not have an accountant. Furthermore, although managers of micro and small enterprises in the municipality of Poção consider accounting information to be important, its use in the decision-making process is not widespread given that their managers generally rely more on their own experience and, in some cases, even on intuition, thus failing to enjoy the benefits that this information can bring to the management of the company.
Keywords: management; micro and small enterprises; accounting information; micro and small companies; micro and small business management; benefits of accounting information